Alternative Media and Taiwan’s Socio-Political Transformation, 1970s–1990s - Hong, Junhao. author. aut Link
XV, 188 p. 1 illus.
Keywords: This book systematically and comprehensively studies on alternative media in Taiwan, using a historical approach and primary data and first hand collected materials to examine how political openness and social movement in the 1980s through the 1990s in Taiwan enabled the rapid growth and wide development of Taiwan’s alternative media, what impact the alternative media in Taiwan had on its socio-political transformation, and what implications Taiwan’s case of alternative media has for other societies, especially for other Asian societies. This book would be a good reading for intellectuals, media professionals, government analysts, and the general public as well, who are interested in this topic. Dr. Junhao Hong is Professor in the Department of Communication at State University of New York at Buffalo, USA. In 1995, he received his PhD in Communication from University of Texas at Austin, USA. His research interests include media and society, international communication and politics, and impact of new media. He has authored/edited a dozen of books and published numerous research articles in various academic journals. Dr. Cheng-Nan Hou is Professor in the Department of Mass Communication at I-Shou University, Taiwan. In 2003, he received his PhD in Communication from State University of New York at Buffalo, USA. His research interests include media and society, social media use, mobile communication technology, and new media and international communication. He has published a number of research articles in various academic journals.